Genetic Prediction of Holstein Breed Cows in The Semi-Arid Region - Araujo, Maria das Dores Silva; de Oliveira, JulioCésar Vieira; Rocha, Laura Leandro da; Alancar, Leonardo Fernandes de; Guido, Sebastiao Inocencio; Filho, Manoel Adriao Gomes (ANIMAL PRODUCTION, 2023)
Molecular genetic assessments are modern selection tools that provide accurate information to producers seeking to improve the health, well-being, and profitability of their herd. The aim of the present study was to elaborate the genomic profile of Holstein cows from the semiarid region of Pernambuco through the Genomic Predicted Transmission Ability values, to correlate milk production characteristics with conformation and reproduction characteristics, and to evaluate information on carriers for genetic diseases. Thirty-nine Holstein cows were used to obtain the Genomic Predicted Transmission Ability-GPTA, a 12k chip (12 thousand genetic markers – CLARIFIDE®) by Zoetis. The averages of GPTA in this study were higher than those of American average, namely 384 pounds of milk production, 17.9 pounds of fat, and 12.9 pounds of protein. For CCS, females showed moderate susceptibility to mastitis. The volume and fat content were considered the most indicated selection criteria to improve the gains in quantity and concentration of solids in milk. Carriers for VMC and CHD were identified. It appeared that the Holstein herd from the semiarid region presented a genetic profile with the potential to improve the productive characteristics, allowing the identification of animals with genetic anomalies before entering the reproductive phase